0005 Bioavailability of supplemental ruminally-protected leucine in sheep. (1st October 2016) - Castro, J. G.; Alford, J. B.; Quinn, K. E.; Lopez, F. A.; Pillmore, S. L.; Scholljegerdes, E. J.; Loest, C. A.
Abstract: The objective of this study was to evaluate the effects of rumen-protected L-Leu on plasma branched-chain AA concentrations and rumen fermentation characteristics of lambs. Four ruminally-cannulated wether lambs (34 ± 2.4 kg BW) were used in a 4 × 4 Latin square. Each period consisted of 7 d: 5 d for adaptation, 1 d for collections, and 1 d of rest. Lambs were fed a basal diet (corn grain and alfalfa hay; 0.6 kg/d DM) and supplements (0.1 kg/d DM) containing no added leucine (CON), 6 g/d of unprotected L-Leu (UP-LEU), and 18 g/d ruminally-protected L-Leu (RP-LEU), or postruminally infused with 6 g/d of L-Leu (INF-LEU). Blood and rumen fluid samples were collected on d 6 of each period at 0, 3, 6, and 9 h after feeding. The statistical model included period, sheep, treatment, hour, and treatment × hour. Lambs receiving INF-LEU had plasma Leu concentrations that were greater at 3 and 6 h, but not different at 9 h compared with CON, UP-LEU, and RP-LEU (treatment × h; P < 0.01). Plasma Ile concentrations were lower for RP-LEU than CON, UP-LEU, and INF-LEU at 0 h, lower for INF-LEU than CON, UP-LEU, RP-LEU and at 3 h, not different among treatments at 6 h, and lower for RP-LEU and INF-LEU than CON and UP-LEU at 9 h (treatment × h, P = 0.02). Rumen fluid acetate (mol/100 mol) tended to be lower for RP-LEU than CON, UP-LEU, and INF-LEU at 0 h, lower for UP-LEU than CON, RP-LEU, and INF-LEU at 3 h, not different among treatments at 6 h, and greater for UP-LEU than CON, RP-LEU, but not INF-LEU, at 9 h (treatment × h, P < 0.01). Rumen isovalerate (mol/100 mol) was greatest for RP-LEU, intermediate for UP-LEU, and lowest for INF-LEU and CON ( P < 0.01). Rumen fluid pH, NH3, total VFA, and molar proportions of propionate, isobutyrate, butyrate, valerate, and acetate:propionate ratio were not altered by treatments ( P ≥ 0.01). Although supplementation of RP-LEU was unable to elevate plasma Leu concentrations, decreases in plasma Ile concentrations are likely due to the antagonistic effects of postabsorptive L-Leu on plasma Ile concentrations. This data implies that the ruminally-protected Leu was absorbed by the gastrointestinal tract of lambs. Altered rumen fermentation also demonstrated that the ruminally-protected L-Leu source was not entirely protected from rumen microorganisms.